A Comparison of Approach and Avoidance Sexual Goals in Couples with Vulvodynia and Community Controls. Issue 11 (27th September 2017) - Dubé, Justin P.; Bergeron, Sophie; Muise, Amy; Impett, Emily A.; Rosen, Natalie O.
Abstract: Background: Provoked vestibulodynia (PVD) is a prevalent form of vulvodynia that interferes with the sexual and relational functioning of affected couples. Approach and avoidance sexual goals are associated with the sexual and relationship well-being of women with PVD and their partners. However, whether sexual goals differ in couples coping with PVD compared with community couples is unknown. Aims: To compare the approach and avoidance sexual goals of women with PVD and their partners with a control sample of community women and their partners to build on an established motivational model and to compare the sexual goals of women with PVD with those of their partners. Methods: Women diagnosed with PVD and their partners (n = 161) and control couples (n = 172) completed measures of approach and avoidance sexual goals. Outcome: Approach and Avoidance Sexual Goals Questionnaire. Results: Women with PVD reported lower approach and higher avoidance sexual goals than control women, whereas partners of women with PVD did not differ from control partners in their sexual goals. Women with PVD also reported lower approach and higher avoidance sexual goals compared with their partners, whereas there were no differences between partners in the control sample. Clinical Implications: Given that avoidance sexual goals have been linked to negative sexual and relational outcomes, clinicians could strive to help couples with PVD become aware of their sexual motives, with the aim of weakening avoidance sexual goals and bolstering approach sexual goals. Strengths and Limitations: This is the first study to empirically document differences in sexual goals between couples affected by PVD and community couples. Limitations include the study's correlational design, differences in demographic characteristics between samples, and the homogeneity of participants' sexual orientation. Conclusions: Findings suggest that the sexual goals of women affected by PVD differ from those of community women and from their partners and support sexual goals as targets for psychological interventions to help couples coping with PVD.